Synthesis and in vitro studies of polycaprolactone-coated superparamagnetic iron oxide nanoparticles for magnetic hyperthermia therapy / Ziba Hedayat Nasab - Ziba Hedayat , Nasab (2020)
Research has garnered a great interest in utilization of superparamagnetic iron oxide nanoparticles (SPIONs) as magnetic nano-heating agents in hyperthermia cancer therapy by profiting from high apoptosis vulnerability of cancer cells at elevated temperatures. However, low oxidation resistance and high agglomeration tendency negatively affect magnetic characteristics of nanoparticles and subsequently their clinical efficiency. Particle surface modifications are potential approaches to endow SPIONs a range of desirable properties including high colloidal dispersity, low aggregation tendency, cytocompatibility, and high oxidation resistance. Currently, polymer coating has led to decrease magnetic hyperthermia efficiency through formation of intermediate layer between nanoheating agents and targeted cells. This research aimed to stabilize the negatively-charged SPIONs through a cationic surfactant, followed by surface coating using thermosensitive biopolymer to improve particles dispersibility, cytocompatibility, functionality and in-vitro cytotoxicity under hyperthermia condition. In this study, synthesis condition was optimized via investigating the effects of two alkaline reagents as well as two synthesis environments on various SPIONs characteristics. Thereafter, the possibility of synthesizing SPIONs using a single iron precursor was examined to decrease synthesis complexity, save expenses, eschew wasting materials and improve their properties. The SPIONs were then stabilized by the surfactant, followed by focusing on preparation of biopolymer-coated SPIONs and assessing their physicochemical, thermal and magnetic properties as well as in-vitro hyperthermia performance on human hepatocellular carcinoma (HepG2) cells under the exposure of an alternating magnetic field (AMF). The obtained resultsindicated that SPIONs could synthesized using a single precursor through precipitation protocol under oxidative experimental condition with significant improvement in crystallinity and magnetic features in comparison with those of SPIONs produced using two precursors. Investigation of the surfactant showed its negligible effect on magnetic behaviors while enhanced dispersibility in a controlled micellar conformation, then biopolymer core-shell SPIONs showed an improvement in hyperthermia efficacy via their enhanced stealth characteristics to avoid rapid clearance by immune system and improved activity towards AMF due to melting of protective shell under hyperthermia condition. The findings indicated that combination of SPIONs and AMF rendered SPIONs highly cytotoxic to liver cancer cells; therefore, they would be a step-change into research as potential targeted nanoheating agent for new therapeutic options.